IMPLEMENTATION OF SCIENCE LEARNING USING COMPUTER BASED INSTRUCTION THROUGH SIMULATION MODELS - Siti Fatonah; Abroto Abroto; Noor Alfi Fajriyani; Eka Putri Ningsih; Irfan Irfan; Kharisma Romadhon (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2022)
The process of implementing Natural Science Learning (IPA) is often said to be a difficult subject so that the decline in student interest in the subject (IPA) can be seen when the student learning process is more passive during learning. The method that is commonly applied is in the form of a lecture method so that the results of the students are more willing to listen during the learning process. The purpose of this study is to determine the implementation of science learning using Computer Based Intruction through a simulation model. The type of research used in this study is qualitative research. Data collection techniques in this study using interviews and documentation. The results of this study describe that at MI Ma'arif Darussalam Plaosan has applied science learning using Computer Based Instuction through a simulation model, namely utilizing visual media in teacher learning has provided more concrete and real learning in learning with the help of visual media. supported by student responses and responses that are very enthusiastic about the learning that is applied, namely based on Computer Based Intruction experienced by students, this has succeeded in supporting student activity. In the simulation model, there are four roles of the teacher, namely: first a teacher explains, second as an intermediary, third as a coach and fourth as a discussion. This simulation learning is four stages which are the stages of orientation, training, simulation and debriefing